PENYELENGGARAAN PEMERINTAHAN DESA DI DESA TIRTA KENCANA KECAMATAN BENGKAYANG KABUPATEN BENGKAYANG - Selviana Yasinta E.42009045 (GOVERNANCE, Jurnal Ilmu Pemerintahan, 2013)
This research uses a qualitative method that uses the theory of Good Governance "UNDP", there are nine important factors to achieve good governance. Of nine of these factors, the author discusses only three factors because they are relevant to the focus of the research that the functioning of the village government and the phenomena that occur in the field. These three factors are: Transparency, Responsiveness, and Accountability.  The problem of this study is the procedure of the village is not working, which is less transparent, accountable, and the response of the village government in carrying out their roles, responsibilities and functions of governance at the village in the village of Tirta Kencana. Research sites in the village of Tirta Kencana. Subjects were heads of government agencies and the empowerment of village, district, village heads, village, village and community consultative body Tirta Kencana. The conclusion of this study is the failure to achieve good governance in village governance in the village of Tirta Kencana because the performance of duties, responsibilities and functions of the government apparatus village less transparent, accountable and responsive, so that the implementation of the government was not in suitable with good governance.Keywords: good governance, administration, village government, and work procedures.